Introduction - Jo Mynard (Studies in Self-Access Learning Journal)
Welcome to the final issue of SiSAL journal for 2022. We are very grateful to everyone who has contributed or participated in the review process this year. Many thanks go to: Dominique Vola Ambinintsoa, Phillip Bennett, Larissa Borges, Bryan Buschner, Ali Dincer, Kerstin Dofs, Daniel Hooper, Satoko Kato, Dennis Koyama, Charlotte Lin, Honggang Liu, Diego Mideros, Ward Peeters, Adelina Ruiz-Guerrero, Ariel Sorensen, Giovanna Tassinari, Andrew Tweed, Isra Wongsarnpigoon, Hisako Yamashita and Amelia Yarwood. Without your work, it would not be possible to publish this journal.